The Consumer Preference and Buying Pattern of Medicines through E-Pharmacy During COVID-19 in Kathmandu Valley - Singtan, Kanchan Tamang (Nepalese Journal of Business, 2024)
This study examines the consumer preference and buying pattern of medicines through e- pharmacy during COVID-19 in Kathmandu valley. Consumer buying behaviour is selected as the dependent variable. Similarly, patient safety, price, consumer loyalty, consumer satisfaction and purchase intention are selected as the independent variables. This study is based on primary data with 145 observations. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing e- pharmacy during COVID-19 in Kathmandu valley. The study showed that patient safety has a positive impact on consumer buying behaviour. It means that increase in patient safety leads to increase in consumer buying behaviour. Similarly, consumer loyalty has a positive impact on consumer buying behaviour. It indicates that increase in consumer loyalty leads to increase in consumer buying behaviour. Moreover, consumer satisfaction has a positive impact on consumer buying behaviour. It means that increase in consumer satisfaction leads to increase in consumer buying behaviour. Likewise, price has a positive impact on consumer buying behaviour. It shows that increase in price leads to increase in consumer buying behaviour. Similarly, price has positive impact on consumer buying behaviour. It shows that higher the price, higher would be the consumer buying behaviour. Further, purchase intention has a positive impact on consumer buying behaviour. It shows that higher the purchase intention, higher would be the consumer buying behaviour.